2012
DOI: 10.1163/187847612x648035
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal correspondences in natural language: Distribution of phonemes and consonant-vowel patterns in Serbian words denoting round and angular objects

Abstract: Since described by Köhler more than half a century ago, phonetic–iconic correspondences have been demonstrated in a series of studies showing remarkable consistency in matches of pseudowords containing specific types of phonemes (e.g., Maluma or Takete) with rounded and angular shapes. If the effect found in these experiments reveals something about processes involved in natural language interpretation, we should expect similar association between phonological properties of objects’ labels and their perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, one of those studies, in which data from 229 languages were analyzed, found certain patterns of language symbolism in majority of those languages (Ciccotosto, 1991). Furthermore, some studies dealing with the structure of words in natural language suggest that words denoting sharp and rounded objects show quite similar patterns of phoneme and consonant-vowel distributions as those found in pseudowords produced for sharp and rounded visual stimuli (Ilić, Ković, & Janković, 2012).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, one of those studies, in which data from 229 languages were analyzed, found certain patterns of language symbolism in majority of those languages (Ciccotosto, 1991). Furthermore, some studies dealing with the structure of words in natural language suggest that words denoting sharp and rounded objects show quite similar patterns of phoneme and consonant-vowel distributions as those found in pseudowords produced for sharp and rounded visual stimuli (Ilić, Ković, & Janković, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Stimuli were selected from the corpus of words used in Ilić, Ković and Janković (2012) and which refered to round or spiky real-objects. Only high-frequent words containing consonantvowel-consonant-vowel-consonant (C-V-C-V-C) structure and referring to concrete objects were recruited from the corpus.…”
Section: Wordsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Congruence Pattern is indicated as * "kiki-type" and O "bouba-type", and ~ "intermediate" according to canonical patterns previously established for Serbian (Ilic, Kovic & Jankovic, 2012).…”
Section: Materials and Stimulimentioning
confidence: 99%